Prototypic chromatin insulator cHS4 protects retroviral transgene from silencing in Schistosoma mansoni - Suttiprapa, Sutas (2011)
Vesicular stomatitis virus glycoprotein (VSVG) pseudotyped murine leukemia virus (MLV) virions can transduce schistosomes, leading to chromosomal integration of reporter transgenes. To develop VSVG-MLV for functional genomics in schistosomes, the influence of the chicken β-globin cHS4 element, a prototypic chromatin insulator, on transgene expression was examined. Plasmid pLNHX encoding the MLV 5′- and 3′-Long Terminal Repeats (LTRs) flanking the neomycin phosphotransferase gene (neo) was modified to include, within the U3 region of the 3′-LTR, active components of cHS4 insulator, the 250 bp core fused to the 400 bp 3′-region. Cultured larvae of Schistosoma mansoni were transduced with virions from producer cells transfected with control or cHS4-bearing plasmids. Schistosomules transduced with cHS4 virions expressed two to 20 times higher levels of neo than controls, while carrying comparable numbers of integrated proviral transgenes. The findings not only demonstrated that cHS4 was active in schistosomes but also they represent the first report of activity of cHS4 in any Lophotrochozoan species, which has significant implications for evolutionary conservation of heterochromatin regulation. The findings advance prospects for transgenesis in functional genomics of the schistosome genome to discover intervention targets because they provide the means to enhance and extend transgene activity including for vector based RNA interference.